Tinjauan Aspek Finansial Penggunaan Mobil Listrik dalam Upaya Mendukung Penurunan Emisi Gas CO2 - Zakarya Nugraha; Novri Kusumathalhah (Jurnal Syntax Transformation, 2022)
ABSTRACT The increase in the price of fuel oil (BBM) in the third quarter of 2022 will have a huge impact on the economy of the community. In addition to inflation, which was also followed by an increase in the price of basic commodities, this also reduced people's mobility in the use of oil-fueled vehicles. The government should use this as a momentum to promote the use of electric vehicles. On the other hand, the price of electric vehicles is still relatively high (expensive) when compared to oil-fueled vehicles. Although from a financial perspective, the use of electric vehicles can be more profitable if it is reviewed within a certain period. This can be shown by the lower cost per kilometer between electric vehicles compared to oil-fueled vehicles. From the point of view of cost comparison analysis over a certain period, the use of electric vehicles is more profitable than oil-fueled vehicles. It is hoped that the tendency of the community can be diverted to using electric vehicles. So that it can indirectly reduce the use of oil-fueled vehicles which is in line with efforts to reduce global warming.